2014
DOI: 10.1186/s12933-014-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic hyperglycemia attenuates sympathetic dysfunction and oxidative stress after myocardial infarction in rats

Abstract: BackgroundPrevious research has demonstrated that hyperglycemia may protect the heart against ischemic injury. The aim of the present study was to investigate the association between hyperglycemia and myocardial infarction on cardiovascular autonomic modulation and cardiac oxidative stress profile in rats. Male Wistar rats were divided into: control (C), diabetic (D), myocardial infarcted (MI) and diabetic infarcted rats (DMI).MethodsDiabetes was induced by streptozotocin (STZ, 50 mg/Kg) at the beginning of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
1
20
0
11
Order By: Relevance
“…Despite the relevance of these findings, this issue deserves further investigation. The response of uncontrolled hyperglycemia on heart remodelling after ischemia is yet to be fully understood [ 2 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relevance of these findings, this issue deserves further investigation. The response of uncontrolled hyperglycemia on heart remodelling after ischemia is yet to be fully understood [ 2 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to a high glucose medium or diabetes for short periods of time has been found to protect the heart against permanent ischemia. This may be due to the improved ventricular function, and reduced infarcted area and mortality reported for diabetic rats under ischemic heart injury [ 7 , 8 , 18 ]. Our group has previously demonstrated that hyperglycemia may promote the survival of heart cells by increasing angiogenesis [ 7 ] and/or by decreasing pro-oxidant damage.…”
Section: Introductionmentioning
confidence: 99%
“…Представленные данные позволяют по-новому взглянуть на проблему СД при сердечно-сосудистой патологии, а также на раскрытие механизмов, обусловливающих повышение устойчивости сердца к ишемическим повреждениям. Как известно, все экспериментальные работы, в которых обнаружен эффект кардиопротекции в условиях развития СД, выполнены на условно молодых животных, что соответствует пациентам трудоспособного возраста, представленным 2 группой в настоящем исследовании [12,13,20,21]. Вместе с тем, как оказалось, стареющие крысы Goto-Kakizaki (модель СД2) имеют повышенную чувствительность к ишемиче-ским повреждениям сердца [22].…”
Section: обсуждение основного результата исследованияunclassified
“…Большое значение в патогенезе развития ишемических повреждений имеет баланс функциональной активности симпатической нервной системы. Так, было обнаружено, что у диабетических крыс снижается дисфункция тонуса симпатической нервной системы, индуцированная инфарктом миокарда, при этом наблюдались повышение антиоксидантной защиты сердца и снижение активности прооксидантных ферментов [21].…”
Section: обсуждение основного результата исследованияunclassified
“…На теперішній час оксидативний стрес розглядають як основний чинник, що поєднує інсулінорезистентність із дисфункцією панкреатичних β-клітин та ендотелію, що створює передумови для застосування антиоксидантів з метою профілактики та лікування метаболічного синдрому та ЦД ІІ типу [10,13,18,21]. У зв'язку з цим одним із перспективних напрямків фармакотерапії ЦД ІІ типу може бути застосування антиоксидантів рослинного походження, зокрема, поліфенолів, яким притаманна висока ефективність у поєднанні з відсутністю виразних побічних ефектів [19,24].…”
Section: вступunclassified